Writing and rootedness in the French Negro-African novel - (:unkn) unknown (My University, 2012)
The African National Literature extent the question of being more or less dynamic implemented. They establish an objective or subjective conception of the nation. Contrary to the XIX th century European National Literatures based on the principle of unity, of language, territory, people, the idea of nation and the African National Literatures seem problematic. In spite of the arbitrary borders and the legal nationalities, inherited from western colonization, the cultural and literatures specificities are observed on the level of African states. For this end, the concept of national literature seems operational when they adhere the cultural areas to the detriment of the African borders (which are) porous and even historically questionable. However the cultural dynamic being evolutionist, isn’t the uncontrolled confinement in the sense of identity source of danger and cultural impoverishment. As a matter of fact, it the identity and the national belongings (memberships) are specific, must them be exclusive? An answer without nuance would be risky in so much as the literary work comes from “an infinite number of variation” of transfers, of imaginaries mergers of the other one in the national literary facts. As such literature and identity objectify themselves as dynamic data which explode the borders, dialogue, ridicule the ideological and arbitrary constructions such as nationalism, regionalism and communitarians. In the African Literary field, it is urgent to free oneself from the scheme of africanity and the fixed national identities. All in all, if the contemporary world falls apart under the thunderstorm of the ambiguous adventures, literature remains the place of brother hood, imaginary mergers and the sharing of cultural and human values.
Keywords: African Research